2021
DOI: 10.1002/poc.4275
|View full text |Cite
|
Sign up to set email alerts
|

Local anesthetics transfer relies on pH differences and affinities toward lipophilic compartments

Abstract: Local anesthetics are weak bases and alter their properties in accordance with their protonation state, which depends on the environmental pH. We studied the transport dynamics of several local anesthetics from the extracellular fluid across biological membranes to the axoplasm, in order to understand the effect of pH on their pharmacodynamic properties. By using experimental pKa values and n‐octanol/water partition coefficients, we calculated pH‐dependent distribution coefficients and therewith associated rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Partition coefficients stemming from experiments 30 or reaction field computations 31 can be used in a thermodynamic model to compute the pH-dependent distribution of anesthetics in detail. 32 While we qualitatively discuss pH effects, the main focus of our work is on the transfer dynamics and its time scale. Below, we make use of the potential of mean force computed in this section and the diffusion coefficient parallel to the lipid layer – as estimated below – to address the time scales of transport in the following two sections.…”
Section: Umbrella Samplingmentioning
confidence: 99%
“…Partition coefficients stemming from experiments 30 or reaction field computations 31 can be used in a thermodynamic model to compute the pH-dependent distribution of anesthetics in detail. 32 While we qualitatively discuss pH effects, the main focus of our work is on the transfer dynamics and its time scale. Below, we make use of the potential of mean force computed in this section and the diffusion coefficient parallel to the lipid layer – as estimated below – to address the time scales of transport in the following two sections.…”
Section: Umbrella Samplingmentioning
confidence: 99%
“…However, high fragility rates may be present in the selected/high-risk patient group who underwent high-volume SIFIB for surgical anesthesia. Additionally, it is known that the intercompartmental transfer of local anesthetic is high in elderly patients [18]. As such, these patients should be accepted as being at high risk for local anesthetic systemic toxicity, and therefore, additional care should be taken by clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…Quantum chemical calculations indicated a plausible reaction between the -C-H group at position 2 ( Figure 1 ) of bupivacaine or ropivacaine and peroxyl radical. Therefore, it is suggested that the most likely reaction mechanism with peroxyl radical in water is the HAT mechanism at position 2, similar to certain flavonoids ( Apak et al, 2013 ) The pKa values of bupivacaine and ropivacaine are 8.21 and 8.16, respectively ( Kavčič et al, 2021b ). Compared to lidocaine, there is a higher proportion of protonated form of the molecule present at the same pH value in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…The lipophilic compartment model suggests that the intramembrane concentration of lidocaine could be 42 times higher than the extracellular concentration due to its high degree of lipid solubility in its neutral form ( Kavčič et al, 2021b ). Please note that the lipid solubility of bupivacaine and ropivacaine is even higher.…”
Section: Discussionmentioning
confidence: 99%